Qawlan Kariman in Tafsir Al-Azhar: Communication Ethics Foundation for Generation Z - Asril Hanapi Hasibuan (Information Technology and Science (ITScience), 2026)
This study aims to analyze the concept of qawlan kar?man in Surah Al-Isr?’ verse 23 based on Tafsir Al-Azhar by Hamka and to examine its relevance as a foundation for communication ethics among Generation Z in the digital era. The research employs a descriptive qualitative approach with a library research design. Primary data were obtained from Surah Al-Isr?’ verse 23 and its interpretation in Tafsir Al-Azhar, while secondary data were derived from contemporary literature on digital communication and Generation Z. Data were analyzed using thematic analysis techniques to identify ethical communication values contained within the exegetical text. The findings indicate that qawlan kar?man encompasses values of verbal politeness, respect for human dignity, emotional self-control, refinement of character, and social moral awareness. From Hamka’s perspective, the nobility of speech is not merely related to word choice but reflects inner quality and moral education. These values demonstrate significant relevance within the context of Generation Z’s digital communication, which is characterized by intense online interaction, rapid expression, and potential verbal conflict. This study concludes that qawlan kar?man can be formulated as a model of digital communication ethics grounded in Qur’anic values, emphasizing moral responsibility, respect for others, and awareness of the social impact of communication. The concept contributes theoretically to the development of Islamic communication ethics studies and practically to strengthening value-based digital literacy.